DETERMINAN KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Siti Qomariyah; Yuni Rimawati; Achdiar Redy Setiawan (Jurnal Akuntansi, 2018)
The aim of this research is to know factors that effect to dividend policy. The population of thisresearch is manufacture companies which listed in Bursa Efek Indonesia for period 2011 – 2015.Sampling technique used is purposive sampling. The total population in this study as many as 141companies and obtained sample as many as 22 companies with 110 observations. Analysis methodused in this research is partial least square (PLS). The results showed profitability have positif effectto dividend policy, while leverage, liquidity, firm size and investment opportunity set has no effect todividend policy. Keywords: Dividend Policy, Profitability, Leverage, Liquidity, Firm Size and Investment Opportunity Set.